Social determination in the health of children born preterm: a scoping review - Mariana Fuentes Mendoza Rodrigues Soares; Amanda de Azevedo Gomes; Juliana Barony da Silva; Luciano Marques dos Santos; Patrícia Pinto Braga; Elysângela Dittz Duarte (Revista Latino-Americana de Enfermagem, 2025)
Objective: to map scientific knowledge on the dimensions of the Social Determinants of Health in the health of children born preterm in the first two years of life. Method: this is a scoping review guided by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. From the studies found in five databases and the reference list of those selected, data was extracted using a coding tool based on the Social Determinants of Health theoretical model with the support of the MaxQDA software. Results: 31 publications were included. The most investigated dimensions of the social determinants of children’s health were related to the characteristics of the individual, with emphasis on health conditions and age, sex, and hereditary factors, highlighting the search for factors that have a direct impact on children’s health. Conclusion: the dimensions of child health most explored were those related to child development. Behavior and living conditions were little investigated. Future studies with a broader approach to the Social Determinants of Health in an integrated way could contribute to the development of care centered on premature infants and early interventions concerning child health outcomes.